2011
DOI: 10.1111/j.1095-8312.2011.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Crassulacean acid metabolism photosynthesis in Bromeliaceae: an evolutionary key innovation

Abstract: Crassulacean acid metabolism (CAM) is a photosynthetic pathway that significantly increases water use efficiency in plants. It has been proposed that CAM photosynthesis, which evolved from the ancestral C3 pathway, has played a role in the diversification of some prominent plant groups because it may have allowed them to colonize and successfully spread into arid or semi-arid environments. However, the hypothesis that CAM photosynthesis constitutes an evolutionary key innovation, thereby enhancing diversificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 45 publications
(79 reference statements)
1
38
0
1
Order By: Relevance
“…Under drought root biomass at bottom was highest in GM-6 (0.414 g) followed by C-15 (0.395 g) and KG-2 (0.392 g) and was lowest in PM-5 (0.124 g), while as under irrigated conditions it was highest in KG-1 (0.399 g) followed by PM-5 (0.273 g) and KG-2 (0.256 g) and was lowest in PM Chari-6 (0.064 g). Root: shoot ratio increases dramatically under drought conditions suggesting that functional responses to reduced soil moisture primarily occur through increased growth of roots, as has been shown suggested by Quezada and Gianoli (2010). Similarly, Huang et al, (2013) also reported that deficiencies of soil water resulted in high root: shoot ratio.…”
Section: Biomass Partitioning Under Greenhouse Conditionsmentioning
confidence: 52%
“…Under drought root biomass at bottom was highest in GM-6 (0.414 g) followed by C-15 (0.395 g) and KG-2 (0.392 g) and was lowest in PM-5 (0.124 g), while as under irrigated conditions it was highest in KG-1 (0.399 g) followed by PM-5 (0.273 g) and KG-2 (0.256 g) and was lowest in PM Chari-6 (0.064 g). Root: shoot ratio increases dramatically under drought conditions suggesting that functional responses to reduced soil moisture primarily occur through increased growth of roots, as has been shown suggested by Quezada and Gianoli (2010). Similarly, Huang et al, (2013) also reported that deficiencies of soil water resulted in high root: shoot ratio.…”
Section: Biomass Partitioning Under Greenhouse Conditionsmentioning
confidence: 52%
“…Without the tank, atmospheric bromeliads (Type IV) have to perform CAM or they will not survive. Therefore, the presence of the tank in some epiphytic bromeliads could be the reason why a clear correlation between CAM and epiphytism was not found in Bromeliaceae, different from other families with epiphytic species [4,68,80].…”
Section: Type IV Bromeliadsmentioning
confidence: 96%
“…In contrast to the Orchidaceae family, however, among bromeliads a strong correlation was not found between the occurrence of CAM and epiphytism [68]. In fact, a more recent work suggested that CAM could be more common in terrestrial, rather than epiphytic, bromeliad species [80]. Although very enlightening, these studies focused on the phylogeny and took into account only whether the plants were epiphytes or not.…”
Section: Cam In Bromeliaceaementioning
confidence: 99%
“…Claims by Quezada and Gianoli (2011) that CAM is associated with higher diversification rates in bromeliads are based on their incorrect identification of four of five sistergroup comparisons they employed.…”
Section: Determinants Of Net Rates Of Species Diversificationmentioning
confidence: 99%